2015
DOI: 10.3758/s13415-015-0375-2
|View full text |Cite
|
Sign up to set email alerts
|

Mindful awareness of feelings increases neural performance monitoring

Abstract: Mindfulness has been associated with enhanced performance monitoring; however, little is known about the processes driving this apparent neurocognitive benefit. Here, we tested whether focusing present-moment awareness toward the nonjudgmental experience of emotion facilitates rapid neural responses to negative performance outcomes (i.e., mistakes). In particular, we compared whether directing present-moment awareness toward emotions or thoughts would enhance the neurophysiological correlates of performance mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 61 publications
5
51
1
3
Order By: Relevance
“…Disgust in response to distressing stimuli, for example, can be reduced by viewing the eliciting scene from a cold, analytical, and emotionless perspective (Gross, 1998). (Saunders, Rodrigo, & Inzlicht, 2016). These results strongly suggest that neural conflict monitoring is systematically moderated by factors that vary the intensity of affect.…”
Section: The Amcc and Valenced Responses To Conflictmentioning
confidence: 54%
“…Disgust in response to distressing stimuli, for example, can be reduced by viewing the eliciting scene from a cold, analytical, and emotionless perspective (Gross, 1998). (Saunders, Rodrigo, & Inzlicht, 2016). These results strongly suggest that neural conflict monitoring is systematically moderated by factors that vary the intensity of affect.…”
Section: The Amcc and Valenced Responses To Conflictmentioning
confidence: 54%
“…For example, a university student cohort exposed to a brief single session of mindful breathing training showed a reduced Pe amplitude but no changes to the ERN (Larson, Steffen, & Primosch, 2013). In contrast, brief single session training in mindful awareness of emotions lead to increased differences in the ERN window between error and correct trials (but no changes in the Pe window) (Saunders, Rodrigo, & Inzlicht, 2016). Within this same study, training to mindful awareness of thoughts showed no changes to either the ERN or Pe (Saunders et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, brief single session training in mindful awareness of emotions lead to increased differences in the ERN window between error and correct trials (but no changes in the Pe window) (Saunders, Rodrigo, & Inzlicht, 2016). Within this same study, training to mindful awareness of thoughts showed no changes to either the ERN or Pe (Saunders et al, 2016). Bing-Canar et al (2016) showed no differences in ERN and Pe amplitudes in university students exposed to a brief single session mindful breathing training.…”
Section: Introductionmentioning
confidence: 99%
“…Enkelte studier har funnet en positiv sammenheng mellom mindfulness og prestasjon på responsinhibisjon (Cheyne et al, 2006;Jha et al, 2015;Jha, Morrison, Parker, & Stanley, 2017;Josefsson & Broberg, 2010;Sahdra et al, 2011;Schmertz, Anderson, & Robins, 2009). Andre studier viser en negativ sammenheng (Larson, Steffen, & Primosch, 2013;Saunders, Rodrigo, & Inzlicht, 2015), eller ingen sammenheng (MacCoon, MacLean, Davidson, Saron, & Lutz, 2014). En mulig forklaring på de motstridene funnene kan vaere at disse studiene har benyttet en samlet mindfulness-score, og ikke skilt mellom de ulike fasettene.…”
Section: Sammenhengen Mellom Mindfulness Og Inhibisjonunclassified
“…Det er heller ikke i tråd med mindfulness-teori (Bishop et al, 2004), selv om enkelte har hevdet at det å innta en ikke-dømmende holdning kan komme i veien for tilstedevaerelse (Rapgay & Bystrisky, 2009). Én mulighet er at motivasjonsmessige faktorer har ført til at respondenter ofrer nøyaktigheten for å respondere raskere på inhibisjonstester (Saunders et al, 2015), for eksempel ved at de som scorer høyt på ikke-dømme, unnlater å gjøre sitt beste, eller at de ikke tar oppgaven på alvor. Det er verdt å nevne at ikke-dømme-fasetten er et element i mindfulness som oppfattes som noe problematisk å forstå verdien av i idrettsmiljøer (Birrer et al, 2012) og andre høyprestasjonsmiljøer .…”
Section: Diskusjonunclassified